Membrane metallo-endopeptidase (Neprilysin) regulates inflammatory response and insulin signaling in white preadipocytes - Alfred K. Ramirez; Simon Dankel; Weikang Cai; Masaji Sakaguchi; Simon Kasif; C. Ronald Kahn (Elsevier, 2019)
Objective: Accumulation of visceral white adipose tissue (WAT) associates with insulin resistance, adipose tissue inflammation, and metabolic syndrome, whereas accumulation of subcutaneous WAT may be protective. We aimed to identify molecular mechanisms that might provide mechanistic insights underlying the phenotypic differences in these tissues. Membrane Metallo-Endopeptidase (MME/Neprislyin) is an extracellular, membrane-bound protease enriched in subcutaneous WAT that can target degradation of a variety of peptides, including insulin, IL6, and β-amyloids. We hypothesized that MME contributes to adipose depot-specific metabolic properties. Methods: We performed RNA sequencing on human subcutaneous and visceral preadipocytes and array gene expression profiling in murine subcutaneous and visceral preadipocytes. We conducted several insulin signaling and inflammatory response experiments on different cellular states of MME expression. Results: MME in white preadipocytes is expressed at a higher level in subcutaneous compared to visceral WAT and favors insulin signaling and a low inflammatory response. Thus, knockdown of MME in subcutaneous preadipocytes increased the inflammatory response to substance P and amyloid β aggregates. This associated with increased basal insulin signaling and decreased insulin-stimulated signaling. Moreover, MME differentially regulates the internalization and turnover of the α/β subunits of the insulin receptor. Conclusion: MME is a novel regulator of the insulin receptor in adipose tissue. Given the clinical significance of both chronic inflammation and insulin sensitivity in metabolic disease, these results show a potentially new target to increase insulin sensitivity and decrease inflammatory susceptibility. Keywords: Insulin receptor, Adipose, Neprilysin, Visceral, Insulin signaling, Inflammation